Chinese Investment in Australia Unique Insights from the Mining Industry - Huang, X. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
This book provides comprehensive coverage on the key issues of Chinese investment in the Australian minerals industry. It offers unique insights into the entry process, the management of Chinese investments, and their success factors and lessons learnt as being impacted upon by the entangling of political, economic, social and competitive forces.